The Relationship of Knowledge Sharing to Employee Performance Moderated by Perceived Supervisor Support - Nazofah Heriad, Resinta; Priyono, Dadang; Gunawan, Asep (Jurnal Ekuisci, 2024)
Knowledge-sharing is an ongoing process, and effective management to create new knowledge is essential for employees to work together as a collective unit and contribute equally to realizing common goals. In addition, if the relationship between employees and knowledge sharing goes well, the employee's performance will increase. Coupled with the Supervisor who supports employees, it can increase morale. This study aims to determine the variables studied: Knowledge Sharing, Employee Performance, and Perceived Supervisor Support. This research uses explanatory research with a quantitative approach. Involving 97 employees of Telkom Akses Cirebon, the results of this study indicate that Knowledge Sharing affects the occurrence of employee performance, and Perceived Supervisor Support moderates the influence of Knowledge Sharing on employee performance on employees of Telkom Akses Cirebon.